Exploitation and Incursion Finding Approach in Various WSW h (International Journal of Innovative Research in Engineering & Management, 2022)
Incursion finding is a process of identifying  and responding malicious activity. Wireless sensor webs consisting bulk of ‘sensors’ are useful to integrate data in variety of environment. The basic sensors are simple and have limited power supplies. Heterogeneous wireless sensor webs are better scalable and lower overall cost  than homogeneous sensor webs. In this paper, we are  improving the lifetime of wireless web and we present a survey of various energy efficient techniques in a various wireless sensor web. It is important to improving wireless web because sensor nodes in wireless webs are constrained by limited energy.
Keywords: Energy efficient; different wireless-web; homogeneous wireless web; Incursion finding; Wireless sensor web; sensors